Annual awards for young researchers in the field of statistical physics and condensed matter theory (Condensed Matter Physics, 2003)
Institute for Condensed Matter Physics of the National Academy of Sciences of
Ukraine announces a new competition for young researchers working in the field
of statistical physics and condensed matter theory. The best works selected by the
Competition Committee will be commended by the Special Awards.